O desenho de capas de discos bossa-novistas e tropicalistas: indicação da cultura brasileira num tempo (1958-1968) - Santana, Valeria Nanci de Macedo (2013)
This research deals with the formulation of a set of analytical techniques for evaluation of vinyl record covers of two of the most important periods of Brazilian music, Bossa Nova and Tropicália. The dissertation was motivated by the general idea that these movements are able to indicate the important role of music to the Brazilian society and the cultural profile of this nation, from 1958 to 1968. Larger stimulus, however, found specifically in: (i) the author's passion for these two musical styles; (ii) personal desire to add more academic work that al-ways current, i.e. graphical analysis to understand given time of a civilization; (iii) academic need to define procedures and analysis techniques for graphical vinyl record covers, long-playing — based on industrial design techniques — that went beyond a mere single, "liked", "cool", "cute". As specific objectives, it was defined: draw a panorama on the graphic-visual languages used by "capistas", i.e., those typographers, artists, graphic designers who designed and illustrated graphically this fascinating industrial product. Sought to contextualize the mus-ical style bossa-tropicalist and released and their productions for the covers of Bossa Nova and Tropicália, understanding the design of the image, from the adequacy in temporal context, demonstrating the importance of proper use of visual language in a record in terms of effects work that seeks to generate; social contribution and academically, various aspects of know-ledge. With that objective in mind, it was treated anterior and posterior aspects to customizing album covers — as it was and as it became the relationship of production "capistas" with the concern on the use of the image. We seek to demonstrate the cultural and aesthetic mark left by these musical periods of the cover designs. We look for references, videos, websites, etc., in addition to data that substantiate this thesis through collaboration (via semi-structured in-terview: forms applied to a sample of twenty interviewees, including broadcasters, musicians, music teachers and music researchers in the city of Feira de Santana-BA); and graphical ana-lyses of the album covers designs from Bossa-nova e Tropicaália; It was sought through me-thods of some theorists, a proprietary method and methods of research subjects, primarily dealing with aspects related to the project factors, types of designs, ideograms and linguistic techniques. We have specified how much the art of drawing and contemplate the disk cover suffered transformations, the advent of the LP to the Era of MP3, mentioning the losses and gains of LP cover designs, while the cultural representation of a time. And how this work may prove to contribute socially, academically and in didactic and knowledge linked to the thematic ordering here. We concluded this research in order to bring up the debate about the possible return of disk cover, and their designs, generating, especially in the music industry, the reflection on the design and making of same.